Robust, Primitive, and Unsupervised Quality Estimation for Segmentation Ensembles - Kofler, Florian; Ezhov, Ivan; Fidon, Lucas; Pirkl, Carolin M.; Paetzold, Johannes C.; Burian, Egon; Pati, Sarthak; El Husseini, Malek; Navarro, Fernando; Shit, Suprosanna; Kirschke, Jan; Bakas, Spyridon; et al. (Frontiers in Neuroscience, 2021)
A multitude of image-based machine learning segmentation and classification algorithms has recently been proposed, offering diagnostic decision support for the identification and characterization of glioma, Covid-19 and many other diseases. Even though these algorithms often outperform human experts in segmentation tasks, their limited reliability, and in particular the inability to detect failure cases, has hindered translation into clinical practice. To address this major shortcoming, we propose an unsupervised quality estimation method for segmentation ensembles. Our primitive solution examines discord in binary segmentation maps to automatically flag segmentation results that are particularly error-prone and therefore require special assessment by human readers. We validate our method both on segmentation of brain glioma in multi-modal magnetic resonance - and of lung lesions in computer tomography images. Additionally, our method provides an adaptive prioritization mechanism to maximize efficacy in use of human expert time by enabling radiologists to focus on the most difficult, yet important cases while maintaining full diagnostic autonomy. Our method offers an intuitive and reliable uncertainty estimation from segmentation ensembles and thereby closes an important gap toward successful translation of automatic segmentation into clinical routine.